Challenges of health care in riverside populations (Research, Society and Development, 2023)
The difficulties related to the few and inefficient actions of public policies include the lack of access to basic public services, such as education and health. Furthermore, the lack of equity has led to serious deficiencies in service delivery and limited health care for the riverside population. Thus, the present study aims to identify the main challenges and problems that hinder health services for the riverside population in general. The present study is an exploratory qualitative research, based on a Systematic Literature Review (SLR), in order to identify relevant publications between the years 2017 and 2021 that determine which factors hinder the population's access to health services. For this, an active search was made for articles that addressed the theme, initially evaluating the title, abstract and later the content in full of the suitable works. The active search for articles in the database resulted in 62 works published in the stipulated period and after applying the inclusion and exclusion criteria, 6 works were able to integrate the results. The authors agree that even today, the biggest problems related to adequate care or provision of health services for the riverside population are found in geographic limitations, however, not necessarily due to location, but due to the lack of structure of the teams involved in providing care.